2015
DOI: 10.5336/medsci.2015-47107
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Risk Factors and Treatment Outcomes of Retinopathy of Prematurity in the Southeastern Anatolian Region Province of Şanlıurfa in Turkey

Abstract: (sırasıyla, p<0,001, p<0,001, p<0,001, p<0,001). S So on nu uç ç: : İlimizde, genel PR görülme sık-lığının (%30) Türkiye ortalamasıyla benzer oranlarda görülmesine rağmen agresif seyirli arka PR (%3) ve şiddetli PR (%12,6) görülme sıklığının yüksek olduğu saptandı. Sunulan sağlık hizmetleri politikasının bir parçası olarak Şanlıurfa'da, PR hastalığını görmeyi tehdit edici seviyelere ulaşma-dan önce saptayabilmek için etkili ve uygun bir tarama programı oluşturulmalıdır.A An na ah h t ta ar r K Ke e l li i m me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(24 reference statements)
0
2
1
Order By: Relevance
“…Özcan et al . [14] reported that the incidence of severe ROP was higher (18%) in neonates with a BW between 1250 and 1500 g than those of the current study. Bas et al .…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Özcan et al . [14] reported that the incidence of severe ROP was higher (18%) in neonates with a BW between 1250 and 1500 g than those of the current study. Bas et al .…”
Section: Discussioncontrasting
confidence: 69%
“…In a study conducted in the same region as the current study, Özcan et al . [14] reported the overall incidence of any stage of ROP as30% and severe ROP as 12%. In the current study, the overall incidence of ROP among Syrian refugees was similar, whereas the incidence of severe ROP was nearly seven times higher than that of infants of Turkish-origin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation